Binder jetting of ceramics: Powders, binders, printing parameters, equipment, and post-treatment. Issue 10 (July 2019) - Lv, Xinyuan; Ye, Fang; Cheng, Laifei; Fan, Shangwu; Liu, Yongsheng
Abstract: Binder jetting is expected to become the universal process for preparing ceramic parts because it can overcome multiple problems, such as the difficulty to prepare complex-shaped ceramic parts and the shrinkage of the sintering process, which appear in conventional ceramic preparation process. This paper introduces principles, steps, and applications of binder jetting printing ceramics. Furthermore, five key factors of binder jetting printing ceramics (powders, binders, printing parameters, equipment, and post-treatment process) have been investigated. Accordingly, effects of powders (including shape, particle size and distribution, and additives), binders (including binding method, droplet-formation mechanism, and droplet-infiltration kinetics), printing parameters (including layer thickness, saturation, solid binder, and printing orientation), equipment, and post-treatment (including de-powdering process, and densification process) on density, roughness, strength, accuracy, and resolution of ceramic parts have been discussed and summarized. This paper provides detailed analysis of techniques and mechanisms of binder jetting of ceramics, giving guidance on how to handle raw materials and select various processing parameters for achieving desired performance.